UJI AKTIVITAS EKSTRAK ETANOL DAUN EKOR NAGA (Rhaphidophora pinnata (L.f.) Schott.) SEBAGAI ANTIHIPERURISEMIA TERHADAP MENCIT PUTIH JANTAN - Bella Pascila; Fathnur Sani K; Revis Asra; Agung Giri Samudra (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Hyperuricemia is a condition of abnormal health hence increasing urid acid level within blood that is up in normal value spesificaly for man is over 7,0 mg/dL and for woman is over 6,0 mg/dL. Ekor naga leaves (Rhaphidophora pinnata L.f.) have some second metabolic compound namely flavonoid and alkaloid that have a capability to hampering xhantine oxidase enzyme. The objective of this reseach is to know the effectiveness giving ethanol extract of ekor naga leaves for decreasing urid acid level and to know the effectiveness dose ethanol extract of ekor naga leaves for decreasing uric acid level. The sample of this reseach was ethanol extract of ekor naga leaves, allopurinol as positive control, chicken liver juice and potassium oxonate as inductioun of hyperuricemia. The design of this research is complete random design with 5 action where in one action consist of 5 mice. The group of action was K+ Allopurinol 0,26mg/kgBB, P1 extract 125mg/kgBB, P2 extract 250mg/kgBB, and P3 extract 375mg/kgBB. The best dose is dose II (250mg/kgBB) with percentage of decreasing uric acid is 45,22%. Than dose III (375 mg/kgBB) with perfentage of dereasing urid acid is 44,66%, and dose I (125 mg/kgBB) with percentage of the decreasing uric acid is 39,60%. Moreover, it can be concluded that all dose of ethanol extract ekor naga leaves have an activity as antyhiperuricemia.